On some problems of the beginning of pre-trial investigation of environmental crimes (Journal of actual problems of jurisprudence, 2018)
The article deals with some procedural, methodological issues decides officials conducting criminal proceedings at the beginning of the pre-trial investigation of environmental crimes developed by representatives of criminology and criminal procedure science. The author emphasizes that criminal cases involving crimes in the sphere of ecology, notes the particular difficulty that affects at the time of inspection, as evidence of a crime is determined by identifying the essential characteristics and requires the use of complex and combination of biological, chemical, physical, economic and even legal activities.Key words: evidence of a crime, pre-trial investigation of environmental crimes, economic and legal measures.